CHANGING PERSPECTIVES ON RESPONSIBLE HERITAGE SITE MANAGEMENT: THE CASE OF LUXOR CITY, EGYPT - Hesham, Eman Shokry; Baller, Inken (História: Questões e Debates, 2018)
This paper aims to enhance critical awareness about the development of heritage site management, specifically focusing on archaeological sites and their adjacent communities in Egypt. To what extent does heritage site management assume responsibility for local communities? For their identity? And for tourism practices? This paper uses the heritage impact assessment tool developed by ICOMOS to assess the management systems and the heritage influence of the UNESCO World Heritage Site “Ancient Thebes with its Necropolis” on the modern-day city of Luxor, Egypt. This tool proposes a set of recommendations for local and national authorities to develop action plans that safeguard the living history of the area around the site. The results suggest ways in which the tool could be improved by enhancing mitigation strategies for tourism-related impacts and re-identifying the variables of Egyptian archaeological sites in order to develop more responsible models of local community identity and visitor awareness.